(untitled) (Semiárida, 2020)
In botanical explorations carried out in Malargüe, 601 specific and infraespecifics taxa were collected, 76 of those are recorded for the first time for Mendoza province, Argentina, Herbarium specimens as a reference, characteristics of habitat and life form are given for each taxon. Common names of some of these taxa based on the oral information obtained from the residents in the studied areas are given.